PEMAHAMAN ORANG MUDA KATOLIK AKAN PENTINGNYA SHARING KITAB SUCI BAGI PERKEMBANGAN IMAN DI STASI YESUS MARIA YOSEP, PENFUI - KUPANG - Taek, Emilia Dolorosa; Hibur, Ursula (Pastoralia Jurnal Penelitian Dosen, 2021)
Sharing the Holy Bible is an activity held by the Church for the development of the faith of all people, both adults and Catholic Young People (OMK). All people are expected to take part in this activity. However, with changing times and increasingly rapid technological advances, OMK's awareness of the importance of participating in Sharing the Holy Book in Basic Community Groups,  the environment and parishes is decreasing. Young Catholics at Jesus Maria Yoseph Station are less active in sharing the Holy Bible because they think that sharing the holy book is just boring and tedious. This is because they do not understand properly and correctly about sharing the Holy Scriptures themselves. The method used in this research is qualitative with a rational empirical approach, prioritizing data analysis from observations and interviews. As a result, sharing the Holy Bible must become a habit so that OMKs love the Holy Bible more as a guide and foundation for Catholic life. Because the activity of sharing the Holy Bible itself aims to raise awareness and increase the Catholic faith in a good and correct way.